Ljudstvo kot dopolnilni varuh, branilec javnih sredstev in subsidiarni tožilec - Rajgelj, Barbara (Teorija in praksa, 2024)
The article analyses the possibilities for strengthening direct democracy in Slovenia as a complement to representative democracy by focusing on improving access to legal remedies in cases where the representative bodies fail to sufficiently protect public interest. It presents the existing mechanisms of direct democracy, such as the petition, referendum and citizens’s legislative initiative, and finds in conclusion that current arrangement often prevents an effective protection of public interest. A lack of trust in the existing representative institutions, the risk of democratic backsliding and a low population’s satisfaction with democracy point to the need for legal remedies that would enable the public to participate more directly in the protection of public goods, human rights, the rule of law, and democracy. Using case studies from three legal areas – constitutional (procedural) law, protection of public funds and criminal (procedural) law – the author proposes three new, alternative legal remedies: the introduction of a constitutional and legal review request initiated by a specified number of voters, a civil lawsuit for the protection of public funds, and the provision of a legal remedy for victims of the criminal offence of public incitement of hatred in cases when the public prosecutor deems there are no grounds to intitiate or continue criminal proceedings.
Keywords: alternative; courts; demokratično nazadovanje; diversity; dostop do pravice; feminisation; gender balance; gender equality; juidiciary; legitimacy; Ljudstvo; neposredna demokracija; popularna tožba; pravna sredstva; Pravo in politika